Buildup of plasma oscillations during modeling the electromagnetic wave propagation - Pavlenko, I.V.; Melnyk, D.A.; Nakonechnyi, M.A.; Girka, I.A. (Вопросы атомной науки и техники, 2016)
A plane wave formation in plasmas is studied numerically by Finite Difference Time Domain (FDTD) solver. The electromagnetic wave is incident normally to the plane boundary between vacuum and isotropic homogeneous plasma. Different harmonics of the plane wave need different time to build up the oscillations in plasma. Therefore a vacuum waveform differs from plasma waveform not due to a difference in dispersions only. The formation of the plane wave in plasma is studied numerically for different points of the dispersion curve known from a plasma steady state theory. The study has to issue finally a numerical model of the plane wave source in plasmas to use it in the problems of plasma wave scattering, tunnelling and conversion.